Flavonoids from leaves of Tetracera scandens L. - Bui, Thanh Tung (Journal of Chemical and Pharmaceutical Research, 2016)
Tetracera scandens L. (Dilleniaceae) is a genus of flowering plants of the Dilleniaceae family. It has been reported that Tetracera scandens L. content hight amout of flavonoids. From the ethanol extract of leaves of Tetracera scandens L, we have been isolated six known flavonoids compounds. Their structures were identified as quercetin-3-O-L-rhamnoside (1), genistein (2), quercetin (3), quercetin 3-O-β-D-glucuronide (4), kaempferol (5) and quercetin-3-O-α-L-arabinofuranoside (6) on the basis of spectroscopic data and by comparing their physicochemical and spectral data with those published in literatures